PENGEMBANGAN MEDIA LAPBOOK “ MAKANANKU” DALAM MENINGKATKAN BERPIKIR KRITIS TERHADAP MAKANAN BERGIZI SEIMBANG PADA USIA 5 – 6 TAHUN - Rizkia Oktavia Putri; Melia Dwi Widayanti; Dhian Gowinda Luh Safitri; Fatiha Khoirotunnisa Elfahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop and examine the practicality and effectiveness of the Makananku lapbook media in improving critical thinking skills regarding balanced nutrition foods among children aged 5–6 years. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The Makananku lapbook was developed as a non-digital learning medium containing various activities designed to foster children's critical thinking skills, including interpretation, analysis, evaluation, and explanation. The participants consisted of 10 children from Group B at TK Negeri Bung Karno Surabaya for instrument testing, 5 kindergarten teachers for the practicality assessment, and 15 children from Group B at TK Negeri Pembina II Surabaya for the effectiveness test. The research instrument was found to be valid and reliable, with a Cronbach’s Alpha coefficient of 0.838. Material expert validation obtained a score of 83%, while media expert validation obtained a score of 93%, indicating that the media was highly feasible. The practicality test showed an average percentage of 96%, categorized as highly practical. The effectiveness test using a one-group pretest-posttest design revealed that the mean pretest score was 11.13 and the mean posttest score was 13.13. The paired sample t-test showed a significance value of 0.001 (p < 0.05), while the Shapiro–Wilk test indicated that the data were normally distributed. Therefore, the Makananku lapbook media was proven to be valid, highly practical, and effective in improving critical thinking skills related to balanced nutrition foods among children aged 5–6 years.